Characterization and whole-genome sequencing of broad-host-range Salmonella-specific bacteriophages for bio-control. (June 2020) - Li, Ping; Zhang, Xiuzhong; Xie, Xianjun; Tu, Zunfang; Gu, Ju; Zhang, Anyun
Abstract: Salmonella Enteritidis ( S. Enteritidis), which could cause human disease and death by consuming the contaminated food, is an important zoonotic pathogen. With the rapid increase of antibiotic resistance all over the world, bacteriophage-based bio-control has gradually attracted public attention widely. In order to find a suitable phage treating S . Enteritidis infection, four phages infecting S . Enteritidis were isolated from poultry fecal samples. Host range showed that four phages had a broad-host-range to Salmonella isolates. The morphological analysis illustrated that all of those phages were classified as the Myoviridae family. The one-step growth curve indicated that bacteriophage BPSELC-1 has a short latent period of about 10 min and a large burst size of 500 pfu/cell in comparison to the other three phages. Then phage BPSELC-1 was sequenced and conducted in vitro experiment. The genome of phage BPSELC-1 is 86, 996 bp in size and has 140 putative genes containing structure proteins-encoding genes, tRNA genes and DNA replication or nucleotide metabolism genes. Importantly, no known virulence-associated, antibiotic and lysogeny-related genes were identified in the genome of BPSELC-1. In vitro experiment of phage treatment pointed out that the number of viable S . Enteritidis ATCC 13076 was reduced by 5.9×log10 at MOI of 10 2 after 4 h. To the best of our knowledge, the phage BPSELC-1 exhibited higher efficiency in S . Enteritidis treatment compared to previous studies. Moreover, it is promising to be used as a broad-spectrum candidate against Salmonella infections in commercial owing to its broad-host-range. Highlights: BPSELC-1 is a broad spectrum bacteriophage of Salmonella. There were no known virulence-associated, antibiotic and lysogeny-related genes identified in the genome of BPSELC-1. Phage BPSELC-1 exhibited higher efficiency in S. Enteritidis treatment compared to previous studies.